2017
DOI: 10.1016/j.jjcc.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Increased aortic stiffness in prepubertal girls with Turner syndrome

Abstract: In prepubertal TS girls, stiffness of the ascending aorta is increased in patients with a BAV and TAV while dilation of the ascending aorta is more frequent in BAV. This suggests an intrinsic aortic wall abnormality making all TS patients at increased risk for severe aortic complications although the risk is the highest for TS with BAV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
32
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 40 publications
5
32
0
Order By: Relevance
“…Carotid-femoral PWV is an integrative measure that reflects the average arterial wall stiffness in the thoracic and abdominal aorta excluding the ascending aorta, the aortic arch and the adjacent descending aorta. Our data are in line with previous studies [45, 46] in the observation that carotid-femoral PWV is comparable between Turner Syndrome and matched controls, suggesting that this part of the aorta is not affected in Turner Syndrome. However, CMR studies evaluating this are lacking.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Carotid-femoral PWV is an integrative measure that reflects the average arterial wall stiffness in the thoracic and abdominal aorta excluding the ascending aorta, the aortic arch and the adjacent descending aorta. Our data are in line with previous studies [45, 46] in the observation that carotid-femoral PWV is comparable between Turner Syndrome and matched controls, suggesting that this part of the aorta is not affected in Turner Syndrome. However, CMR studies evaluating this are lacking.…”
Section: Discussionsupporting
confidence: 93%
“…Smaller studies in children and young adults with Turner Syndrome previously showed increased PWV and a greater Aix compared to controls [45, 46]. The present study finds that adults with Turner Syndrome have a raised Aix but comparable PWV.…”
Section: Discussionsupporting
confidence: 69%
“…Old age and the presence of BAV are also associated with aortic diameters . Although one study reported no association between BP and aortic growth during 2.4 years of follow‐up, several studies have reported hypertension to be an important and modifiable risk factor for aortic dilation . In particular, systolic BP was associated with aortic distensibility in patients with TS .…”
Section: Discussionmentioning
confidence: 99%
“…For all patients with TS, cardiac evaluation should be performed at diagnosis and regularly followed up at 3‐ to 5‐year intervals in adulthood to facilitate early detection of aortic disease . Patients with TS have a higher risk for aortic dilation due to inherent vasculopathy and/or oestrogen deficiency . According to a recent guideline, the use of Turner‐specific z ‐scores is recommended, particularly for those under 16 years old.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first broadly based investigation showing a significant correlation of deteriorated aortic elasticity values to TS only in a wide age range spectrum of pediatric TS patients, especially after exclusion of patients with aortic dilatation, CoA and BAVs. Another study showing pathological elasticity levels in TS children independent of their aortic valve morphology [ 24 ] excluded adolescents due to a suspected negative influence of HRT as well as children below 6 years of age because of lesser cooperation, presenting a study population of only 15 patients. The same group presented an MRI study verifying these findings in a bigger study cohort, but including adult patients in a great amount as well [ 25 ].…”
Section: Discussionmentioning
confidence: 99%